The golden proportion among Malay students in IIUM/ Malaysia - Abdul Majeed, Kais Raad; Mustafa, Ammar A.; Al-Marzok, Maan Ibrahim; Ibrahim, Ibrahim Khalil (2013)
The maxillary anterior teeth are significant in achieving beautiful dental aesthetics. This study aimed to find the application of golden proportion on Malaysian populations. Materials and methods: The sample size consisted of 100 students from any faculty, 50 men and 50 women, ranging in age from 20 to 25 years old. The subjects have all of their natural anterior teeth, no history of orthodontic treatment or tooth size alteration and are of Malay origin. Impression was taken and measurements done by using cast. The golden percentage calculated by dividing the width of each central incisor, lateral incisor and canine by the total width of all six maxillary anterior teeth, multiplied by 100 in order to obtain the golden percentage for each tooth. The golden proportion found to be accurate between the width of the right central and lateral incisors in 33.2% of men and 33.1% of women subjects. 13.9% of male and 13.6% of female subjects have the widths of their right lateral incisors in golden proportion to the widths of their right canines. Moreover, the data shows 37.2% of the male and 37.1% of the female subjects have the widths of their left central incisors in golden proportion to the widths of the eft lateral incisors Golden proportion is applicable to Malay population. The width of the central incisor represents 24%, lateral incisor 16% and canine 10% of the width of the six maxillary anterior teeth as viewed from the front.